On New Mathematical Modeling Measuring the Band Gap of Semiconductor in Nanomaterial - Salem, Aisha (Journal of Science and Technology, 2020)
The magnitude and character components (M&C) band gap energy of semiconductor composite nanomaterial (SCN) is framed in this effort. The theoretical preparations supported by the energy increased by spacing the atoms in a crystalline state (solid energy) of the nano crystals compared to the bulk crystals. CdTe, CdSe, ZnSe, ZnTe and ZnS semiconductor composites were deliberated for the investigation of M&C components band gap dynamism. In addition, an entropy definition was employed in terms of this energy. It is confirmed that the band gap (BG) energy of SCN is subjected to the atom magnitude and character. From the layout, it can be concluded that the band gap energy increases whenever the atomic magnitude of the semiconductor nanomaterial reducing. The results attained were associated with the obtainable experimental information, which sustain the ability of the layout described.